Preface to special topic: frontiers on THz photonic devices - Atakaramians, S; Johnston, M; Padilla, W; Mendis, R (AIP Publishing, 2018)
Terahertz (THz) photonic devices are now exploiting emerging materials systems, while novel device designs utilise plasmonic effects, nanophotinics, and metamaterials. The scope of this special topic highlights and reviews the recent cutting-edge THz photonic devices which have been revolutionised from the advances in the above research areas.